Odpowiedzi

Najlepsza Odpowiedź!
2009-12-04T17:50:02+01:00
A) x + 2 y = - 13 //* 2
2 x + 4 y = - 26

b) 3 x + y = -5 //* 2/3
2 x + (2/3) y = - 10 / 3

c) - x - 4 y = 2 //* (- 2)
2 x + 8 y = - 4

d) x - ½ y = 1 //* 2
2 x - y = 2

e) 3 x - 3 y = 1 //* 2/3
2 x - 2 y = 2/3

f) x + ¾ y = 0 //* 2
2 x + (6/4) y = 0

Pozdro)
2009-12-04T17:50:56+01:00
A) x+2y= -13 / ×2
2x + 4y = - 26

b)3x+y= -5 /÷3
x + ⅓y = -5/3 / × 2
2x + ⅔y = - 3⅓

c)-x-4y= 2 / ×2
-2x - 8y = 4 / -1
2x + 8y = -4

d)x-½y= 1 / ×2
2x - y = 2

e)3x-3y= 1 /÷3
x - y = ⅓ / ×2
2x - 2y =⅖

f)x+¾y= 0 / ×2
2x + 1½ = 0
2009-12-04T17:53:44+01:00
A) x+2y= -13 /*2
2x+4y=-26

b)3x+y= -5 /* ⅔
2x+⅔y=-3⅓

c)-x-4y= 2 /*(-2)
2x+8y=-4

d)x-½y= 1/*2
2x-y=2

e)3x-3y= 1/*⅔
2x-2y=⅔

f)x+¾y= 0 /*2
2x+1½y=0